2013
DOI: 10.1523/jneurosci.3482-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neural Changes with Tactile Learning Reflect Decision-Level Reweighting of Perceptual Readout

Abstract: Despite considerable work, the neural basis of perceptual learning remains uncertain. For visual learning, although some studies suggested that changes in early sensory representations are responsible, other studies point to decision-level reweighting of perceptual readout. These competing possibilities have not been examined in other sensory systems, investigating which could help resolve the issue. Here we report a study of human tactile microspatial learning in which participants achieved >six-fold decline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 98 publications
3
57
3
Order By: Relevance
“…In many applications, lagged methods for effective connectivity in fMRI are applied to the deconvolved BOLD time series, with an example of GC (David et al., 2008; Goodyear et al., 2016; Hutcheson et al., 2015; Ryali, Supekar, Chen, & Menon, 2011; Ryali et al., 2016; Sathian, Deshpande, & Stilla, 2013; Wheelock et al., 2014). However, as demonstrated in Figure 5b, the natural variability in the neuronal dynamics results with an upper bound on the accuracy of the lagged based methods: even assuming a perfect deconvolution (which is never the case in practice), which would allow for perfect retrieval of the neuronal time series from the BOLD time series, for the TR = 0.70 s, the accuracy rate of ∆ would be <100% (for the parameter space we are exploring in this study, this accuracy would be on the level of 90%).…”
Section: Discussionmentioning
confidence: 99%
“…In many applications, lagged methods for effective connectivity in fMRI are applied to the deconvolved BOLD time series, with an example of GC (David et al., 2008; Goodyear et al., 2016; Hutcheson et al., 2015; Ryali, Supekar, Chen, & Menon, 2011; Ryali et al., 2016; Sathian, Deshpande, & Stilla, 2013; Wheelock et al., 2014). However, as demonstrated in Figure 5b, the natural variability in the neuronal dynamics results with an upper bound on the accuracy of the lagged based methods: even assuming a perfect deconvolution (which is never the case in practice), which would allow for perfect retrieval of the neuronal time series from the BOLD time series, for the TR = 0.70 s, the accuracy rate of ∆ would be <100% (for the parameter space we are exploring in this study, this accuracy would be on the level of 90%).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, Sathian et al (2013) found no evidence for SI changes following tactile perceptual learning when looking at changes in functional connectivity in the human brain. They trained subjects in a microspatial tactile task producing a six-fold reduction in tactile acuity thresholds.…”
Section: What Is the Nature Of The Neurocognitive Mechanism Supportinmentioning
confidence: 91%
“…I will discuss how these experimental modulations of perception have informed our understanding of supportive neural mechanisms, and what they reveal about dynamic plasticity of somatosensory perception in response to experience (Adab & Vogels, 2011;Law & Gold, 2008A. Reed et al, 2011;Sathian, Deshpande, & Stilla, 2013). Finally, I will outline areas where gaps still exist in our understanding and how research conducted in the current thesis attempts to address outstanding questions.…”
Section: Brief Summary Of Thesis Contentmentioning
confidence: 97%
See 2 more Smart Citations